Pregnancy: An Underutilized Window of Opportunity to Improve Long-term Maternal and Infant Health—An Appeal for Continuous Family Care and Interdisciplinary Communication - Arabin, Birgit; Baschat, Ahmet A. (Frontiers in Pediatrics, 2017)
Physiologic adaptations during pregnancy unmask a woman’s predisposition to diseases. Complications are increasingly predicted by first-trimester algorithms, amplify a pre-existing maternal phenotype and accelerate risks for chronic diseases in the offspring up to adulthood (Barker hypothesis). Recent evidence suggests that vice versa, pregnancy diseases also indicate maternal and even grandparent’s risks for chronic diseases (reverse Barker hypothesis). Pub-Med and Embase were reviewed for Mesh-terms „fetal programming” „and „pregnancy complications combined with maternal disease” until January 2017. Studies linking pregnancy complications to future cardiovascular, metabolic and thrombotic risks for mother and offspring were reviewed. Women with a history of miscarriage, fetal growth restriction, pre-eclampsia, preterm delivery, obesity, excessive gestational weight gain, gestational diabetes, subfertility and thrombophilia more frequently demonstrate with echocardiographic abnormalities, higher fasting insulin, lipids, or deviating clotting factors and show defective endothelial function. Thrombophilia hints to thrombotic risks in later life. Pregnancy abnormalities correlate with future cardiovascular and metabolic complications and earlier mortality. Conversely, women with a normal pregnancy have lower rates of subsequent diseases than the general female population creating the term: “Pregnancy as a window for future health”. Although the placenta works as a gatekeeper, many pregnancy complications may lead to sickness and earlier death in later life when the child becomes an adult. The epigenetic mechanisms and the mismatch between pre- and postnatal life have created the term “fetal origin of adult disease”. Up to now, the impact of cardiovascular, metabolic or thrombotic risk profiles has been investigated separately for mother and child. In this manuscript, we strive to illustrate the consequences for both, fetus and mother within a cohesive perspective and thus try to demonstrate the complex interrelationship of genetics and epigenetics for long-term health of societies and future generations. Maternal-fetal medicine specialists should have a key role in the prevention of non-communicable diseases by implementing a framework for patient consultation and interdisciplinary networks. Health care providers and policy makers should increasingly invest in a stratified primary prevention and follow-up to reduce the increasing number of manifest cardiovascular and metabolic diseases and to prevent waste of health care resources.